Interventional cohort study of prolonged use (>72 hours) of paracetamol in neonates: protocol of the PARASHUTE study - Sissel Sundell Haslund-Krog; Steen Hertel; Kim Dalhoff; Susanne Poulsen; Ulla Christensen; Diana Wilkins; John van den Anker; Tine Brink Henriksen; Helle Holst (BMJ Publishing Group, 2019)
Introduction Anticipated or actual pain in neonates results in use of paracetamol for prolonged pain relief in many neonatal intensive care units. Clinical trials examining safety of paracetamol exposure in neonates have been of short duration (1-3 days) and hepatic biomarkers and paracetamol metabolism are rarely reported in the same studies.We aim to investigate the safety (hepatic tolerance) and effectiveness of prolonged paracetamol exposure in neonates by measuring hepatic biomarkers, plasma concentrations of paracetamol and its metabolites and pain scores. In addition, we study a possible interaction between ethanol and paracetamol.Methods and analysis A multicentre interventional cohort study.Neonates of any gestational age and up to 44 weeks postmenstrual age, treated with oral or intravenous paracetamol can be included.Alanine aminotransferase (ALT) and bilirubin are measured at baseline or within 24 hours after treatment initiation. P-paracetamol and metabolites are measured at steady state and every 2 days (opportunistically) together with ALT and bilirubin and lastly after discontinuation of treatment. COMFORT neo pain scores are collected longitudinally. COMFORT neo pain scores and population pharmacokinetic analysis of paracetamol samples will be analysed simultaneously using non-linear mixed effects models. One and two compartment models with first-order elimination will be tested for disposition. In addition, plasma ethanol is measured if the patient receives concomitant treatment with intravenous or oral phenobarbital containing ethanol as an excipient.Ethics and dissemination Inclusion of patients can be postponed 24 hours after the first paracetamol dose. This is intended to make the inclusion process less stressful for parents. This study uses standard dosing strategies. The potential risks are additional blood samples, which are collected opportunistically to reduce additional heel pricks.Trial registrationnumber Ethics Comittee: H-17027244, EudraCT no: 2017-002724-25, BFH-2017-106, 05952.